PENGARUH RELATIONSHIP MARKETING DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN (Studi Pada Hotel Sapadia Kecamatan Pasir Pengaraian) - Triyana Putri; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of relationship marketing and corporate imageon customer loyalty at the Hotel Sapadia Districts Pasir Pengaraian. Relationship marketingas a variable (X1) corporate image as a variable (X2) and customer loyalty as a variable (Y).The method in this research is descriptive and quantitative using SPSS, wheresamples were used that guests staying more than 3 times in the Hotel Sapadia Districts PasirPengaraian with respondents as many 99 people. To determine the number of samples usedslovin formula, as well as a sampling technique by purposive sampling. Data collectionthrough questionnaires and interviews.Results of analysis using multiple linear simple, using multiple linear regression, ttest and f test so that it can be seen that the variable relationship marketing positive effect oncustomer loyalty, that the provision of corporate image significant effect on customer loyaltyand significant relationship marketing and corporate image on customer loyalty.Keywords: Relationship Marketing, Corporate Image and Customer Loyalty.